Virtual reality set-up for studying vestibular function during head impulse test - Desoche, Clément; Verdelet, Grégoire; Salemme, Romeo; Farnè, Alessandro; Pélisson, Denis; Froment, Caroline; Hermann, Ruben (Frontiers in Neurology, 2023)
Objectives Virtual reality (VR) offers an ecological setting and the possibility of altered visual feedback during head movements useful for vestibular research and treatment of vestibular disorders. There is however no data quantifying vestibulo-ocular reflex (VOR) during head impulse test (HIT) in VR. The main objective of this study is to assess the feasibility and performance of eye and head movement measurements of healthy subjects in a VR environment during high velocity horizontal head rotation (VR-HIT) under a normal visual feedback condition. The secondary objective is to establish the feasibility of VR-HIT recordings in the same group of normal subjects but under altered visual feedback conditions. Design Twelve healthy subjects underwent video HIT using both a standard setup (vHIT) and VR-HIT. In VR, eye and head positions were recorded by using, respectively, an imbedded eye tracker and an infrared motion tracker. Subjects were tested under four conditions, one reproducing normal visual feedback and three simulating an altered gain or direction of visual feedback. During these three altered conditions the movement of the visual scene relative to the head movement was decreased in amplitude by 50% (half), was nullified (freeze) or was inverted in direction (inverse). Results Eye and head motion recording during normal visual feedback as well as during all 3 altered conditions was successful. There was no significant difference in VOR gain in VR-HIT between normal, half, freeze and inverse conditions. In the normal condition, VOR gain was significantly but slightly (by 3%) different for VR-HIT and vHIT. Duration and amplitude of head impulses were significantly greater in VR-HIT than in vHIT. In all three altered VR-HIT conditions, covert saccades were present in approximatively one out of four trials. Conclusion Our VR setup allowed high quality recording of eye and head data during head impulse test under normal and altered visual feedback conditions. This setup could be used to investigate compensation mechanisms in vestibular hypofunction, to elicit adaptation of VOR in ecological settings or to allow objective evaluation of VR-based vestibular rehabilitation.